2017
DOI: 10.1007/s00011-017-1080-0
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 regulates insulin-resistant proteins to increase apoptosis in the mouse retina

Abstract: Objective and Design Work in multiple organs has suggested that toll-like receptor 4 (TLR4) may play a role in insulin resistance. Additional studies have shown a negative role for TLR4 on retinal health. We have previously reported that β-adrenergic receptors can regulate both TLR4 signal transduction, as well as insulin signaling in the retina and in retinal endothelial cells (REC). Thus, we hypothesized that TLR4 would regulate retinal insulin signaling. Materials and Methods We used endothelial cell spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…1b, d). These data agree with the genotyping and Western blot results for whole retina reported previously [22]. …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…1b, d). These data agree with the genotyping and Western blot results for whole retina reported previously [22]. …”
Section: Resultssupporting
confidence: 93%
“…At 3 months of age, the TLR4 floxed and TLR4 Cre-Lox mice were used for experiments. Genotyping and Western blot results for TLR4 from these mice have been recently published [22]. …”
Section: Methodsmentioning
confidence: 99%
“…All of the changes induced by high glucose were reduced/reversed when cells were treated with TLR4 siRNA, suggesting that high glucose induced TLR4 to mediate dysfunctional insulin signaling in retinal Müller cells. These findings agree with our previous work in Müller cells, as well as others work in other retinal cell types (9, 16). Future work will include making the Müller cell specific knockout mice diabetic with a high fat diet to better mimic type 2 diabetes in vivo .…”
Section: Discussionsupporting
confidence: 94%
“…We recently reported that endothelial cell specific knockout of TLR4 led to improved insulin signaling (9), which was not observed in TLR4 overexpressing mice. For this study, we wanted to combine our previous studies on retinal Müller cells and insulin signaling to investigate the actions of TLR4 in retinal Müller cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation